Importance of Biometals as Targets in Medicinal Chemistry: An Overview about the Role of Zinc (II) Chelating Agents - Rosalba Leuci; Leonardo Brunetti; Antonio Laghezza; Fulvio Loiodice; Paolo Tortorella; Luca Piemontese (Applied Sciences, 2020)
Zinc (II) is an important biometal in human physiology. Moreover, in the last two decades, it was deeply studied for its involvement in several pathological states. In particular, the regulation of its concentration in synaptic clefts can be fundamental for the treatment of neurodegenerative diseases, such as Alzheimer’s disease (AD). Zinc (II) is also a constituent of metalloenzymes (i.e., matrix metalloproteinases, MMPs, and carbonic anhydrases, CAs) with catalytic function; therefore, it can be an important target for the inhibition of these proteins, frequently involved in cancer onset. This review is focused on the significance of zinc (II) chelating agents in past and future medicinal chemistry research, and on the importance of selectivity in order to revamp the possibility of their use in therapy, often hindered by possible side effects.